Examined the Energy-Led Growth Hypothesis in India: Evidence from Time Series Analysis - Behera, Jaganath (Energy Economics Letters, 2015)
The present study examined the linkage between energy consumption and economic growth in India uses the annual time series data covering the period from 1970-71 to 2011-12. The study used Gross Domestic Product as a proxy for economic growth and energy consumption (oil equivalent per capital). The empirical findings of the study suggest that there is both the short run and the long run relationship exist between energy consumption and economic growth. The Granger causality result confirms that there is unidirectional causality running from economic growth to energy consumption. That means the study support the conservation hypothesis. The impulse response result of the study suggests that India requires an alternative source of energy for faster economic growth. The variance decomposition of the study concluded that the rapid growth of the economy depends on the heavy energy consumption. From the policy recommendation point of view, the energy policy of India should give more importance to find out the alternative source of energy supply in order to meet the growing demand for energy. Moreover, to achieve sustainable energy conservation and macroeconomics stable India should follow the energy efficiency and self-sufficiency in energy production for faster economic growth.